Inhibitory effect of mulberry (Morus alba) polyphenol on the lipid and protein oxidation of dried minced pork slices during heat processing and storage. (May 2018) - Xu, Liang; Zhu, Ming-Jun; Liu, Xue-Ming; Cheng, Jing-Rong
Abstract: This study aims to assess the antioxidant efficacy of mulberry ( Morus alba ) polyphenol (MP) in vacuum-packed dried minced pork slices stored at room temperature for 20 days. Dried minced pork slices were manufactured with 20 g/kg, 40 g/kg MP or 0.2 g/kg BHT, respectively. The results presented that MP significantly reduced TBRAS values increment and carbonyls formation while decelerated sulfhydryl losses in dried minced pork slices. Dried minced pork slices manufactured with MP gained higher a * value ( P  < .05) and lower L * value ( P  < .05) than the control. In additional, MP also improved microbiological stability and sensory properties of dried minced pork slices during storage. All these results demonstrated that MP as a natural antioxidant might have remarkable potentiality in meat products. Highlights: Antioxidant effect of dried minced pork slices with mulberry polyphenol was studied. Mulberry polyphenol retarded lipid and protein oxidation in dried minced pork slices. Inhibitory effect of mulberry polyphenol on microbes of dried minced pork slices. Mulberry polyphenol improved sensory properties of dried minced pork slice.